Political Storytelling on Instagram: Key Aspects of Alexander Van der Bellen’s Successful 2016 Presidential Election Campaign - Liebhart, Karin (2017)
This article addresses the strategic use of Instagram in election campaigns for the office of the Austrian Federal President in 2016. Based on a comprehensive visual analysis of 504 Instagram posts from Green-backed but independent presidential candidate Alexander Van der Bellen, who resulted as winner after almost one year of campaigning, this contribution reconstructs key aspects of digital storytelling on Instagram. By identifying relevant image types central to the self-representation of the candidate, this article shows how a politician makes use of a digital platform in order to project and manage desired images. The salience of image types allows for the reconstruction of underlying visual strategies: (1) the highlighting of the candidate’s biography (biographical strategy), (2) the presentation of his campaign team (team strategy), and (3) the presentation of the candidate as a legitimate office holder (incumbent strategy). The article thus sheds light on visual aspects of digital storytelling as relevant factor of political communication.